Peran Taruna Sebagai Agen Indonesia Youth Road Safety Warrior Guna Peningkatan Pemahaman Remaja Tentang Safety Riding - Putu Eka Suartawan; Budi Mardikawati (Universitas Darunnajah, Jakarta, Indonesia, 2023)
The increase in the number of accidents is caused by human error. The aim of the cadets' activities as agents of the Indonesian Youth Road Safety Warrior is to receive and continue driving safety material through campaign activities. The method is direct socialization. The target of the campaign is 35 students from State High School 1, Kediri, Tabanan-Bali. Before implementation, cadets took part in driving safety training in Sidoarjo, accompanied by instructors from Astra Honda Motor and Bali Land Transportation Polytechnic Lecturers. Furthermore, the material is distributed through driving safety campaigns. Material includes inspection, equipment, body posture when driving, and accident factors. The implementation of the campaign takes the form of providing a pretest, material, posttest, and practice in the field. The results obtained showed that the cadets were able to receive and transmit the driving safety material well. The students' enthusiasm was visible, and there was a significant difference between the pretest and posttest scores using the Wilcoxon test. Increasing student understanding is an indication of the success of the cadets' role as Indonesian Youth Road Safety Warrior agents.